Development, good governance and human rights - Sharma, B.M.; Sharma, Abhishek (2014)
References are always made to the importance of human rights but there has been little conceptual work devoted to the relationship between human rights and development programmes and projects, and translating this into actual work in the field. A human rights approach to development provides development workers broader but precise concepts and guidelines to address and integrate these rights in their work. Development, especially sustainable development, is important in the context of human rights. For being sustainable it must provide individuals with secure and predictable long-term access to the resources required to satisfy their needs and improve their well-being. The process of sustainable development implicitly involves working progressively to secure the rights of individuals to resources-economic, social, cultural, political and civil. - Reproduced.
Keywords: Human rights; Good governance; Public administration